STUDENTS’ LEARNING STYLE AND READING COMPREHENSION ACHIEVEMENT: A CORRELATIONAL ANALYSIS - Endang Aprilia; Nita Ria; Yuyun Hendrety (Didascein : Journal of English Education, 2022)
This study aimed at finding out whether there was significant correlation between students’ learning style and reading comprehension achievement. It utilized correlational research method. The eleventh-graders of Madrasah Aliyah Negeri 2 Palembang in academic year 2020/2021 were the population of the study.  The sample was 107 students selected by using purposive sampling technique. Students’ learning style questionnaire and reading comprehension test were the instruments for collecting data. Both instruments were validated before they were distributed to the sample. The data were analyzed using Pearson product moment. The finding revealed that there was no significant correlation between students’ learning style and reading comprehension achievement of the eleventh graders of Madrasah Aliyah Negeri 2 Palembang since the p-value (0.845) was lower than 0.05. The rvalue was 0,024, which showed that there was low correlation between students’ learning style and reading comprehension achievement of the eleventh-grade students of Madrasah Aliyah Negeri 2 Palembang. Based on the finding, it can be concluded that the students’ learning style did not give dominant effect to reading comprehension achievement. It is shown that there was no significant correlation between students’ learning style and their reading comprehension achievement of the eleventh graders of Madrasah Aliyah Negeri 2 Palembang.